(untitled) (Journal of Science and Technology, 2016)
Hydropower plants in Ghana have suffered several low level operations within the past two decades. This paper looks at optimum operations of the plants during these low level conditions. The two hydropower plants are located along the Volta River at Akosombo and Kpong. The Akosombo plant is at the upstream such that its discharge creates available head for the Kpong plant which is downstream. The Akosombo plant is designed to operate between the levels of 75.59m minimum and 84.12m maximum while the Kpong plant operates between 14.5m and 17.7m. The mode of unit combinations for optimum power generation is determined in this paper. This could serve as a guide in operating the two Hydropower plants. The method presented could also function as a power prediction tool during the low level conditions at Akosombo (i.e. below 75.59m).